2021
DOI: 10.1111/aas.13787
|View full text |Cite
|
Sign up to set email alerts
|

A combination of infraclavicular and suprascapular nerve blocks for total shoulder arthroplasty: A case series

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The incidence of HDP following different approaches of ICB is relatively low, which is 3% during the classical approach of ICB with 20 mL LA, [6] 15% after retroclavicular block with 25 mL LA, [7] and 2.5% to 5% after CCB (a new infraclavicular approach targeting the three cords that could provide sufficient analgesia for shoulder surgery by retrograde diffusion of LA to the supraclavicular nerve) with 20 to 30 mL LA, respectively [3,8] . The combination of ICB and anterior suprascapular block for shoulder surgery yielded an HDP rate of 5% [9] . The superior trunk block, a new block developed to minimize the involvement of the phrenic nerve by injecting LA next to the upper trunk of the brachial plexus (prior to the separation of the suprascapular nerve), has an HDP rate of 4.8% [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of HDP following different approaches of ICB is relatively low, which is 3% during the classical approach of ICB with 20 mL LA, [6] 15% after retroclavicular block with 25 mL LA, [7] and 2.5% to 5% after CCB (a new infraclavicular approach targeting the three cords that could provide sufficient analgesia for shoulder surgery by retrograde diffusion of LA to the supraclavicular nerve) with 20 to 30 mL LA, respectively [3,8] . The combination of ICB and anterior suprascapular block for shoulder surgery yielded an HDP rate of 5% [9] . The superior trunk block, a new block developed to minimize the involvement of the phrenic nerve by injecting LA next to the upper trunk of the brachial plexus (prior to the separation of the suprascapular nerve), has an HDP rate of 4.8% [10] .…”
Section: Discussionmentioning
confidence: 99%
“…[3,8] The combination of ICB and anterior suprascapular block for shoulder surgery yielded an HDP rate of 5%. [9] The superior trunk block, a new block developed to minimize the involvement of the phrenic nerve by injecting LA next to the upper trunk of the brachial plexus (prior to the separation of the suprascapular nerve), has an HDP rate of 4.8%. [10] Axillary tunnel catheter indwelling to avoid phrenic nerve block still resulted in a 1.5% incidence of HDP.…”
Section: Retrospective Analysismentioning
confidence: 99%
“…The sample size is calculated at 90% power and based on variation in the NRS for pain for the study population using the formula [ 8 ], \begin{document}n = \kappa \frac{\left (Z _{\alpha }+ Z_{\beta } \right )^{2} \left ( \sigma ^{2} \right )}{d^{2}}\end{document} , where \begin{document}\sigma\end{document} = 3.0, the IQR of the maximum score on the NRS for pain; d = 30% of median score on the NRS for pain (=6.5), the difference considered to be clinically significant; design effect \begin{document}\kappa\end{document} = 1; type I error α = 5% corresponding to a 95% confidence level, type II error β = 10% for detecting results with 90% power of study. So, the required sample size is n = 31 for each group.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size is calculated at 90% power and based on variation in the NRS for pain for the study population using the formula [8],…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…A single patient (5%) experienced hemi-diaphragmatic paralysis. Musso et al [48] reported no interscalene block technique resulted in a risk of hemi-diaphragmatic paralysis less than 27%.…”
Section: Infraclavicular Brachial Plexus Block Combined With Suprasca...mentioning
confidence: 99%